Tacrolimus Reverses UVB Irradiation-Induced Epidermal Langerhans Cell Reduction by Inhibiting TNF-α Secretion in Keratinocytes via Regulation of NF-κB/p65 - Xu, JiaLi; Feng, YaDong; Song, GuoXin; Gong, QiXing; Yin, Li; Hu, YingYing; Luo, Dan; Yin, ZhiQiang (Frontiers in Pharmacology, 2018)
Background: Topical calcineurin inhibitors including tacrolimus and pimecrolimus are used in the treatment of many inflammatory skin diseases mainly via blocking T-cell proliferation. Our previous studies found pimecrolimus 1% cream could reverse high-dose ultraviolet B (UVB) irradiation-induced epidermal Langerhans cells (LCs) reduction via inhibition of LCs migration. We conducted this study to investigate the effects of topical tacrolimus 0.03% ointment on high-dose UVB- irradiated human epidermal LCs. Methods: Twenty fresh human foreskin tissues were randomly divided into 4 groups as follows: Control, Tacrolimus (0.03%), UVB (180 mJ/cm2 ), and UVB (180 mJ/cm2 ) + Tacrolimus (0.03%). Four time points were set as follows: 0h, 18 h, 24h, and 48h. We collected culture medium and tissues at each time point. The percentage of CD1a+ cells in the medium was detected by means of flow cytometry. Each tissue was prepared for immunohistochemistry, real-time quantitative PCR and western blot. HaCaT cells were cultured and divided into 4 groups: Control, Tacrolimus (1ug/ml), UVB (30mJ/cm2), and UVB (30mJ/cm2)+ Tacrolimus (1ug/ml). The cells were incubated for 24 h and prepared for real-time quantitative PCR and western blot. Results: Topical tacrolimus significantly reversed high-dose UVB irradiation-induced epidermal LCs reduction and CD1a+ cells increment in culture medium. Tacrolimus significantly inhibited UVB irradiation-induced tumor necrosis factor-α (TNF-α) and nuclear factor kappa B (NF-κB)/p65 mRNA and protein expression in HaCaT cells. Tacrolimus also significantly inhibited high-dose UVB irradiation-induced TNF-α expression in cultured tissues. Finally, TNF-α antagonist (recombinant human TNF-α receptorⅡ: IgG Fc fusion protein) could significantly reverse UVB irradiation-induced epidermal LCs reduction. Conclusion: Topical tacrolimus 0.03% could reverse UVB irradiation-induced epidermal LCs reduction by inhibiting TNF-α secretion in keratinocytes via regulation of NF-κB/p65.